2021
DOI: 10.3390/ijms22168621
|View full text |Cite
|
Sign up to set email alerts
|

Silver Nanoparticles Derived by Artemisia arborescens Reveal Anticancer and Apoptosis-Inducing Effects

Abstract: The fight against cancer is one of the main challenges for medical research. Recently, nanotechnology has made significant progress, providing possibilities for developing innovative nanomaterials to overcome the common limitations of current therapies. In this context, silver nanoparticles (AgNPs) represent a promising nano-tool able to offer interesting applications for cancer research. Following this path, we combined the silver proprieties with Artemisia arborescens characteristics, producing novel nanopar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…This confirms that MU-AgNPs can cause the tumor cells to death through apoptotic pathway. Our data matches with the other reports who has used different plant AgNP extracts ( Bordoni et al, 2021 ). Finally, mitochondrial membrane potential studies confirmed the reduction of cell viability through apoptosis process, thus staining with JC-1 dye confirmed that MU-AgNPs treated group has shown high intensity thus confers the breakdown of mitochondrial membrane and results in lower membrane potential.…”
Section: Discussionsupporting
confidence: 93%
“…This confirms that MU-AgNPs can cause the tumor cells to death through apoptotic pathway. Our data matches with the other reports who has used different plant AgNP extracts ( Bordoni et al, 2021 ). Finally, mitochondrial membrane potential studies confirmed the reduction of cell viability through apoptosis process, thus staining with JC-1 dye confirmed that MU-AgNPs treated group has shown high intensity thus confers the breakdown of mitochondrial membrane and results in lower membrane potential.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have also shown different species of Artemisia in various cancer cells [ 47 , 48 , 49 , 50 ]. In addition, the green synthesized nanoparticles from different Artemisia species are also reported to exert antiproliferative effects on cancer cells mediated through apoptotic cell death [ 23 , 51 , 52 ]. A study by Sahu, Meena, Shukla, Chaturvedi, Kumar, Datta, and Arya [ 24 ] indicated that ethyl acetate and hexane fractions of A. nilagirica induced cell death in colon, lung, and breast cancer cells.…”
Section: Resultsmentioning
confidence: 99%
“…The different species of the genus were found to have strong antibacterial and antifungal properties against pathogenic organisms in humans, livestock, and plants [ 16 , 17 , 18 , 19 , 20 ]. Antiproliferative and apoptotic effects are attributed to the bioactive compounds and extracts of various species of Artemisia [ 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are previously known publications on silver nanoparticles formation in such Artemisia plants, as A. absinthium [56], A. arborescens [57], A. vulgaris [58], A. turcomanica [59], A. sieberi [60], A. afra [61], A. capillaris [62], A. scoporia [63], A. marschalliana [64], A. haussknechtii [65], A. annua [66], and A. tilesii [36]. However, those studies were focused on the characterization of nanoparticles, namely their yield, concentration and size distribution, as well as the antioxidant and reducing potential of obtained nanoparticles and their biomedical applications.…”
Section: Discussionmentioning
confidence: 99%